The Influence of Leadership Style,Organizational Culture, Job Satisfaction on Employee Performance in RSUD Dr Soetomo Surabaya - Pratama, Dikky Julistian; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to examine the influence of Leadership Style, Organizational Culture and Job Satisfaction on employee performance at RSUD Dr Soetomo Surabaya . The approach used in this research is a quantitative approach and data were collected through questionnaires to employees. The data obtained was analyzed using SEM analysis technique with totaling 97 respondents. Respondent is a 97 employee at RSUD Dr Soetomo with various division. Data Collection instrument meansured on a likert scale. The results obtained leadership style, organizational culture, and job satisfaction have a significant direct and indirect effect on employee performance in the Environment RSUD Dr Soetomo Surabaya. results highlight effective leadership style, which provides clear direction and supports employees, as well as an organizational culture that is positive, inclusive, and supports innovation, has a direct impact on employee performance